Effects of medroxyprogesterone acetate (MPA) in activating progesterone receptor signaling in benign and cancer-associated fibroblasts of the endometrium - Chung, I.; Omar, I.S.; Adenan, N.A.; Woo, Y.L. (2017)
MedroxyprOgesterone acetate (MPA) is used for conservative treatment for endometrial cancer (EC); however, patients often develop progesterone resistance. Most typical and atypical endometrial hyperplasia shows regression after MPA treatment Primary type 1 .EC responds moderately to MFA therapy (50-70%). Yet, MPA treatment only o ffe rs 10-20% response rates and survival of less than one year in advanced and recurrent Fe. It was shown that secretion from normal fibroblast cells inhibit while cancer 'fibroblasts cells promote the proliferation of EC cells. Interestingly, a recent study showed that progesterone receptor (PH.) expression in normal fibroblast is important for progesterone inhibitory effects on cancer cells. It has also been shown that estrogen is responsible for increasing PR expression. However, it is still largely unknown, if and how, fibroblasts from endometrial cancers modulate EC response to progesterone. BAF and CAF were isolated from human endometrial primary cultured cells using antibody-conjugated. magnetic beads. Fibroblast and epithelial markers expression, and progesterone receptor (PR) expression were determined using quantitative real-time peR (qRT-PCR) and western blotting, PR nuclear translocation was determines using immunofluorescence assay. Cell viability was determined using MTT assay. Fibroblasts expressed high levels of fibroblast markers but not epithelial cell markers indicating minimal epithelial cells contamination. Both BAP and CAl: expressed varied levels of PR expression. PR nuclear translocation occurs within 6 hours of 10 nM MPA treatment in RAPs and CAFs. Their response to MFA growth inhibition was similar (20% growth inhibition when compared to vehicle) after treated with 1-400 oM MPA for 72 hours. The cell viability was 22% and 9% lower in BAFs and CAPs, respectively following 100 nM MPA treatment in the presence of 10 nIV!E2 compared to MPA alone. Our data suggests that PR signaling in CAP can be activated, and but has lower response to combination of MPA and estrogen treatment.